COMPARATIVE EVALUATION OF INTRATHECAL BUPIVACAINE (0.5% HEAVY) WITH MIDAZOLAM 1 MG VERSUS 2 MG AS AN ADJUVANT IN SUBARACHNOID BLOCK FOR ELECTIVE LOWER ABDOMINAL SURGERIES (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Spinal anaesthesia is widely used for lower abdominal surgeries due to its rapid onset and effective analgesia. However, limited duration of action remains a concern. Intrathecal midazolam, acting via GABA receptors, has been shown to enhance analgesic effects when used as an adjuvant to bupivacaine. This study aims to compare the efficacy and safety of two doses (1 mg and 2 mg) of intrathecal midazolam combined with 0.5% hyperbaric bupivacaine. Methods: 80 patients (ASA I–II, aged. 18–60) undergoing elective lower abdomen operations participated in a prospective, randomised, single-centre trial. Two groups of patients were created: bupivacaine and 1 mg of midazolam were given to Group M1, while bupivacaine and 2 mg of midazolam were given to Group M2. The onset and duration of sensory and motor block, sedation scores, time to rescue analgesia, haemodynamic alterations, and side effects were among the parameters evaluated. The t-test and chi-square test were used for statistical analysis, with significance set at p